Fatty liver disease might increase the risk of abdominal operation in patients with fatty liver and the prevalence of cancer in first-degree relatives (Retracted article. See vol. 26, pg. 290, 2015) - BAŞARANOĞLU, METİN; Basaranoglu, METİN; UYSAL, ÖMER; Canbakan, Billur; ŞENTÜRK, HAKAN; YILDIZ, Kemal; CEYLAN, Bahadir; BAYSAL, Birol; Uysal, Omer; Senturk, HAKAN (My University, 2014)
Background/Aims: We investigated the risk of abdominal operation in patients with fatty liver and the risk of any cancer in first-degree relatives of patients with fatty liver.